2017
DOI: 10.1186/s40793-017-0234-6
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of four strains of Corynebacterium pseudotuberculosis bv. Equi isolated from horses showing distinct signs of infection

Abstract: The genomes of four strains (MB11, MB14, MB30, and MB66) of the species Corynebacterium pseudotuberculosis biovar equi were sequenced on the Ion Torrent PGM platform, completely assembled, and their gene content and structure were analyzed. The strains were isolated from horses with distinct signs of infection, including ulcerative lymphangitis, external abscesses on the chest, or internal abscesses on the liver, kidneys, and lungs. The average size of the genomes was 2.3 Mbp, with 2169 (Strain MB11) to 2235 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The respective percentages of the predicted coding regions are: 86.16% on MEX1, 86.33% on MEX9, 85.94% on MEX25 , 86.66% on MEX29 , 83.06% on MEX30 and 86.64% on MEX31 . These genome sizes and the G + C content (~ 52%) are consistent with other C. pseudotuberculosis studies [ 2 , 6 , 52 ]. There are 64 predicted RNA genes in strains of the biovar ovis (MEX1, MEX9, MEX25 and MEX29 ) and 66 from the biovar equi ( MEX30 and MEX31 ).…”
Section: Genome Propertiessupporting
confidence: 91%
“…The respective percentages of the predicted coding regions are: 86.16% on MEX1, 86.33% on MEX9, 85.94% on MEX25 , 86.66% on MEX29 , 83.06% on MEX30 and 86.64% on MEX31 . These genome sizes and the G + C content (~ 52%) are consistent with other C. pseudotuberculosis studies [ 2 , 6 , 52 ]. There are 64 predicted RNA genes in strains of the biovar ovis (MEX1, MEX9, MEX25 and MEX29 ) and 66 from the biovar equi ( MEX30 and MEX31 ).…”
Section: Genome Propertiessupporting
confidence: 91%
“…Other diphtheria‐like organisms identified in animals include biovar C. diphtheriae subsp. belfanti , C. ulcerans , C. rouxii , C. uterequi , and C. pseudotuberculosis (Baraúna et al., 2017; Corboz et al., 1996; Oliveira et al., 2014; Rückert et al., 2015; Schlez et al., 2021; Sing et al., 2016; Zendri et al., 2021). However, classic diphtheria is rare in animals.…”
Section: Introductionmentioning
confidence: 99%
“…The varied DNA fragments are due to rpoB polymorphism among species (Khamis et al 2004). Because of the polymorphism, several studies have used the partial rpoB sequences and showed that the partial rpoB has the superior ability for differentiating Corynebacterium species and useful for taxonomic classification (Khamis et al 2005;Gomila et al 2012;Venezia et al 2012;Baraúna et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Several genes can be used for the identification of Corynebacterium species, including rpoB, gyrA, and 16S rRNA genes (Khamis et al 2005;Gomila et al 2012;Venezia et al 2012;Baraúna et al 2017). Among these genes, the rpoB gene is considered as a gold standard for the identification of Corynebacterium species (Zasada and Mosiej 2018).…”
Section: Introductionmentioning
confidence: 99%